The Global Financial System’s New Tool: Digital Money - Dayi, Faruk (Springer International Publishing, 2019)
The developments in information and internet technology have led to profound changes in the global financial system. In the new financial system, modern financial instrument are used more than conventional money and financial instruments. With the emergence of new financial instruments, economic and financial crises were experienced in both money and capital markets and significant structural problems were observed in the economy. Those who believed that the financial system caused the crisis of 2008 were in search of a new financial system. Satoshi Nakamoto, about one and a half months after the crisis with encryption technique invented a highly reliable currency that eliminates intermediary service as a solution to many problems caused by real money, which allows monetary parties to conduct their transactions directly. Cryptocurrency technology aims to make transactions reliable and provide money control with the encryption technique. Due to the high security encryption technique of the network structure it is not possible to infiltrate into the system. In addition to being reliable, the new currency recently has been more effective as an investment tool rather than being a medium of exchange in daily life anywhere in the world. In order to increase the use of cryptocurrencies serious infrastructural preparation is needed. Therefore, its use for investment purposes has become widespread. The use of cryptocurrencies as a financial instrument and their impact on the money and capital markets remain to be seen.
Keywords: 8. Economic growth